From Algorithmic Logic to Pneumatological Presence : A Theological and Statistical Discernment of AI in the FJKM Homiletic Context - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2026)
The rapid integration of generative artificial intelligence (AI) into homiletic and liturgical practices marks a "change of era" for the contemporary Church, necessitating a rigorous interdisciplinary evaluation of its spiritual and ontological implications. This study investigates the tension between the functional efficiency of Large Language Models (LLMs) and the traditional understanding of preaching as an embodied, pneumatological event. By synthesizing systematic theology—grounded in the Thomistic distinction between ratio and intellectus and Barthian pneumatology—with empirical sociological analysis, the research evaluates whether algorithmic mediation facilitates or disrupts the authentic proclamation of the Word. Central to this inquiry is an original empirical survey conducted in April 2026 within the Fiangonan’i Jesoa Kristy eto Madagasikara (FJKM), involving N=67 pastors and lay leaders. Quantitative analysis, utilizing a one-way ANOVA, was employed to test the null hypothesis concerning differences in perception between clergy and laity regarding AI as a substitute for the Holy Spirit. The results yielded a p-value of 0.412, indicating a remarkable ecclesial consensus : while 81% of respondents acknowledge the functional utility of AI, a profound 91% reject it as a pneumatological replacement. Furthermore, 87% of participants advocated for a dedicated digital commission, signaling an urgent demand for institutional governance. This study concludes by proposing a "theological discernment framework" based on six guiding principles, asserting that AI must remain an "exegetical orthosis" under qualified human supervision, thereby preserving the sacred, incarnate, and testimonial nature of the ministerial vocation against the risks of technological "enslavement."